Activation-induced NKT cell hyporesponsiveness protects from α-galactosylceramide hepatitis and is independent of active transregulatory factors - Biburger, Markus; Tiegs, Gisa (Journal of Leukocyte Biology, 2008)
NK T (NKT) cells, unique lymphocytes expressing features of NK and T lymphocytes, can specifically be activated with the glycolipid antigen α-galactosylceramide (α-GalCer). In humans and mice, this activation provokes pronounced cytokine responses. In C57BL/6 mice, α-GalCer injection additionally induces NKT-mediated liver injury, representing a model for immune-mediated hepatitis in humans. However, a single α-GalCer pretreatment of mice prevented NKT-mediated liver injury, cytokine responses (systemically and locally in the liver), and up-regulation of hepatocellular Fas upon α-GalCer rechallenge. As α-Gal-Cer is used as a NKT cell-activating agent in clinical trials, an investigation of tolerance induction appears crucial. We demonstrate that α-GalCer tolerance does not depend on Kupffer cells, IL-10, Caspase-3-mediated apoptosis, or CD4 CD25 T regulatory cells (T), which are crucial in other models of immunological tolerance. Amending relevant, earlier approaches of others, we cocultivated highly purified, nontolerized and tolerized liver NKT cells ex vivo and could convincingly exclude the relevance of transdominant NKT T. These results strongly suggest α-GalCer-induced tolerance to be exclusively caused by NKT cell intrinsic hyporesponsiveness. Tolerized mice showed specific diminishment of the intrahepatic CD4 NKT cell subpopulation, with the CD4 population largely unaffected, and revealed downmodulation of α-GalCer-specific TCR and the NKT costimulator glucocorticoid-induced TNFR-related protein on liver NKT cells, whereas inhibitory Ly49I was increased. In conclusion, α-GalCer tolerance could serve as a model for the frequently observed NKT cell hyporesponsiveness in tumor patients and might help to develop strategies for their reactivation. Conversely, approaches to render NKT cells hyporesponsive may constitute new therapeutic strategies for diseases, where aberrant NKT cell activation is causally involved. © Society for Leukocyte Biology.
Keywords: Anergy; Animal models; Liver immunology; Lymphocytes; Natural killer T cells; Tolerance